A study on prevalence and risk factors of hearing impairment among newborns - James, Mary; P., Kumar; Ninan, Praveen Jacob (International Journal of Contemporary Pediatrics, 2018)
Background: Hearing impairment in children constitutes a particularly serious obstacle to their optimal development. Early detection of hearing impairment is vital since early intervention including hearing aids and speech therapy can be initiated at the earliest and will help them to enjoy equal opportunities in society alongside all other children. The aim of the study was to determine the prevalence and risk factors associated with hearing impairment among newborns delivered in a tertiary care centre using a two staged OAE test. Methods: This study was a prospective descriptive study done in Govt. T.D. medical college, Alappuzha over a period of 12 months. All newborns (4359) were included in the study. They were carefully evaluated for presence of risk factors and OAE was done before discharge from the hospital. If found abnormal OAE was repeated at 6 weeks, failing which BERA was performed. Results: Out of 4268 newborns screened, 275 failed OAE (6.4%) and 44 failed second OAE (1.03%) also. BERA was done in 40 newborns out of whom 6 failed (prevalence of 1.3 per 1000 population). Risk factors studied were prematurity, perinatal asphyxia, hyperbilirubinemea requiring phototherapy, congenital infection, family history of deafness, NICU admission more than 5 days, culture positive sepsis and newborns receiving ototoxic medications. Conclusions: Hearing impairment was more among those with risk factors. But hearing evaluation is important in all newborns irrespective of presence of risk factors to avoid missing hearing impairment in otherwise normal newborn.